Turbina oblongata Protects Against Oxidative Cardiotoxicity by Suppressing Lipid Dysmetabolism and Modulating Cardiometabolic Activities Linked to Cardiac Dysfunctions - Erukainure, Ochuko L.; Chukwuma, Chika I.; Matsabisa, Motlalepula G.; Javu, Mirranda T.; Salau, Veronica F.; Koorbanally, Neil A.; Islam, Md. Shahidul (Frontiers in Pharmacology, 2021)
Cardiotoxicity leading to cardiovascular dysfunction and ultimately cardiac failure remains a major global health issue irrespective of race, age and country. Several factors including lipotoxicity, oxidative imbalance, exacerbated angiotensin-converting enzyme (ACE) activity and altered bioenergetics have been implicated in the pathophysiology of cardiovascular diseases. Turbina oblongata (E. Mey. ex Choisy) A. Meeuse is among the medicinal plants commonly used traditionally in the treatment and management of various ailments including cardiovascular dysfunctions in South Africa. In the present study, T. oblongata was investigated for its cardioprotective mechanism on oxidative-mediated cardiotoxicity by determining its effect on redox imbalance, purinergic and cholinergic dysfunction, and ACE activity as well as lipid dysmetabolism and pathways in iron-induced oxidative cardiac injury. Oxidative injury was induced ex vivo in freshly isolated heart by incubating with 0.1 mM FeSO4. Treatment was done by co-incubating with T. oblongata extract or gallic acid which served as the standard antioxidant. Induction of oxidative cardiac injury led to significant depleted levels of glutathione, triglyceride, HDL-cholesterol, superoxide, catalase and ENTPDase activities, with concomitant elevated levels of malondialdehyde, cholesterol, LDL-cholesterol, ACE, acetylcholinesterase, ATPase and lipase activities. These levels and activities were significantly reversed following treatment with T. oblongata. Induction of oxidative injury also caused alterations in lipid metabolites, with concomitant activation of beta oxidation of very long chain fatty acids, plasmalogen synthesis and mitochondrial beta-oxidation of long chain saturated fatty acids pathways. Some of the altered metabolites were restored following treatment with T. oblongata, with concomitant inactivation of beta oxidation of very long chain fatty acid pathway. These results indicate the cardioprotective effect of T. oblongata against oxidative-mediated cardiotoxicity. This is evidenced by its ability to mitigate lipotoxicity and modulate dysregulated cardiometabolic activities as portrayed by its antioxidative activity and suppressive effects on ACE, acetylcholinesterase and lipase activities, while modulating cardiac lipid dysmetabolism.